1987
DOI: 10.1088/0031-9155/32/2/002
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of intracellular alkali metals in Reference Man

Abstract: A review of recent literature and a re-analysis of data used in Publication 23 of the International Commission on Radiological Protection (ICRP) have revealed several problems regarding the distribution of the predominantly intracellular alkali metals potassium, rubidium and caesium in ICRP Reference Man. In this paper we re-evaluate the distribution of the intracellular alkali metals in humans and we offer an approach for selecting reference concentrations for the organs of a typical adult human. For non-skel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

1988
1988
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 58 publications
0
32
0
Order By: Relevance
“…Previously, the authors reexamined the organ masses and the steady-state distributions of K, Rb and Cs in a typical 70-kg adult male, age 35 y (Williams and Leggett 1987;Leggett and Williams 1986). Pertinent features of this reference male are summarized in Table 1.…”
Section: The Rb Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, the authors reexamined the organ masses and the steady-state distributions of K, Rb and Cs in a typical 70-kg adult male, age 35 y (Williams and Leggett 1987;Leggett and Williams 1986). Pertinent features of this reference male are summarized in Table 1.…”
Section: The Rb Modelmentioning
confidence: 99%
“…Despite the large amount of physiological and medical information available on Rb, there does not exist a model that tracks the timedependent distribution of this element in the body over an extended period with much detail or accuracy. For example, the retention model for Rb given in Publication 30 of the International Commission on Radiological Protection (ICRP 1979) inaccurately portrays the skeleton as the tissue with the highest Rb concentration (Williams and Leggett 1987). Also, the ICRP model views all non-skeletal tissues as a single compartment and thus cannot accurately depict the heterogeneous distribution of Rb in soft tissues at early times (Ryan et al 1985 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Various investigations showed that K and Cs have many common properties but some tissues and organs discriminate quantitatively between those elements. Comprehensive studies concerning the distribution of alkali elements in humans were published by Williams and Leggett (1987) and Leggett et al (2003).…”
Section: Introductionmentioning
confidence: 99%
“…Cesium enters easily into the plant and animal systems and is deposited in soft tissues [12]. The total content of this intracellular form is very low, no more than 0.00131 g [13].…”
Section: Basic Information On Cesiummentioning
confidence: 99%